Frequency of Neurogenic Strabismus in Al-Ibrahim Eye Hospital, Karachi - Muhammad Qasim, Shua Azam Priyanka (Pakistan Journal of Ophthalmology, 2019)
Purpose: To determine the frequency of Neurogenic Strabismus presenting at the Orthoptics Clinic in Al-Ibrahim Eye Hospital, Malir Karachi. Study Design: Cross-sectional study. Sampling Technique: Non-probability convenient sampling. Place and Duration of Study: Orthoptics Clinic of Al-Ibrahim Eye Hospital (AIEH) Karachi, Pakistan from May to October, 2018. Material and Methods: This study included 349 subjects age ranged from 5 to 75 years. All ocular examinations for strabismus were performed, including cover test, prism cover test and Hess chart. Demographic features and etiologies were recorded, and the causes of extra ocular muscle palsies were grouped as; trauma, diabetes, hypertension and others. SPSS version 20.0 was used to analyze the data. Results: Frequency of neurogenic strabismus was found to be 6%. Out of 21 subjects, 8 (38.1%) subjects had diabetes, followed by 2 (9.5%) subjects with hypertension, 5 (23.8%) subjects with ocular trauma and 6 (28.6%) subjects with other causes. The most commonly affected side was the right eye seen in 13 (61.9%) subjects. The most common ocular motor nerve involved was abducent (sixth) nerve in 13 (61.9%) subjects, followed by oculomotor (third) nerve in 4 (19%) subjects. Out of the patients with third nerve palsy 3 (14.3%) subjects had pupil sparing and only 1 (4.8%) subject had no pupil sparing. Conclusion: Sixth nerve was the most common nerve involved and most common etiology was uncontrolled diabetes. Keywords: Neurogenic Strabismus, Cranial nerve palsies, Paralytic strabismus